Morphological features and the strength-speed fitness of female volleyballers at a high sports level - Marcin Krawczyk; Mariusz Pociecha; Paulina Kozioł; Aleksandra Stepek; Ryszard Guzy; Krzysztof Więcek; Krzysztof Rzepa (University of Applied Sciences in Tarnow, Poland, 2019)
Introduction: Modern volleyball requires players to present a high level of strength and speed fitness. Efficiency in this discipline is also significantly determined by the level of development of the somatic features, including especially body height and shoulder range. The main aim of the study was to assess the level of development of the most important morpho-functional features characterizing female volleyball players at high sports level against the background of non-training women. Material and methods: 13 female players representing the 1st league volleyball club took part in the research. The control group consisted of 11 women not exercising any form of competitive sport. Measurements of basic somatic features were carried out: body height, body weight and its tissue components. In addition, explosive strength of the lower limbs tests (CMJ) and the Wingate test was performed. On the basis of statistical analysis, the most important somatic features and motor fitness indicators characterizing I-league volleyballers were selected. Results: The greatest differences between volleyball players and non-training women in terms of morphological features was recorded for lean body mass (LBM [kg], Z = 6.63, p <0.01). However, in terms of motor fitness indicators, the largest differences were found in terms of peak power, average power and CMJ [cm] and CMJ power [W/kg]. Calculated, respectively: Z = 2.59, p <0.001; Z = 3.22, p <0.001; Z = 2.75, p <0.001, Z = 2.54, p <0.001). Conclusions: Our research confirmed importance of selected morpho-functional features conducive to high efficiency of Female's volleyball. Jumping tests (e.g. CMJ) assessing the motor potential of lower limbs of volleyball players have practical value in the context of recruitment, selection and control of female's volleyball training. The Wingate test, as a diagnostic tool, can be used as an adjunct to retinal specific tests.